Robotics as a Tool for Deconstructing Stereotypes in Amazon: Disseminating Information in Baixo Trombetas - Sousa, Luciana; Coimbra, Raiane; Pantoja, Leana; Santos, Eliene; Cardoso, Queilane; Cativo, Crystian; Monteiro, Suzane; Monteiro, Flavia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This article highlights the importance of technology with a focus on robotics to assist in the educational development of children, adolescents and the community in general in Amazon. For this, it was proposed a project called Cunhantã ++ who used robotics education in schools from kindergarten, which was not foreseen at its beginning, through high school / technical education to increase interest and break down barriers caused primarily by mathematics and logic fear.To combat these problems that are linked to different gender and race stereotypes, a project was created focused on bringing the Amazonian female audience closer to robotics using an intuitive and attractive methodology through events such as exhibitions, festivals, competitions, seeking to arouse interest urban and traditional populations (indigenous, quilombolas and riverside). The methodology enabled teachers and the general public in programming and Arduino, starting with Scratch, Python and C languages, respectively. Another project highlight was the active presence of undergraduate students, raising their self-esteem and improving their academic performance. As results and actions developed, the group can highlight scientific articles publications, fairs and exhibitions in public elementary schools, technology events in a quilombola community, held for the first time in the city of the Brazilian Informatics Olympics (OBI), being the city with the most enrolled schools in the State of Para. As it is a competition more accessible to the realities of public schools in the cities, as it does not need infrastructure and equipment, and it was extremely important for the insertion of students in the world of school competitions and to show the potential of investment in robotics for the school directors. There was also an excellent result with two girls reaching the national stage in the Junior Scientific Initiation modality, in addition to the regional selection of a group formed only by elementary school girls with their own robotics project at the Science and Technology Fair of Baixo Amazonas Mesoregion.